Molecular characterisation of the tick rhipicephalus microplus in Malaysia: new insights into the cryptic diversity and distinct genetic assemblages throughout the world - Van Lun Low; Sun Tee Tay; Kai Ling Kho; Fui Xian Koh; Tiong Kai Tan; Yvonne Ai Lian Lim; Bee Lee Ong; Chandrawathani Panchadcharam; Yusoff Norma-Rashid; Mohd Sofian-Azirun (2015)
The morphotaxonomy of Rhipicephalus microplus complex has been challenged in the last few years and prompted many biologists to adopt a DNA-based method for distinguishing the members of this group. In the present study, we used a mitochondrial DNA analysis to characterise the genetic assemblages, population structure and dispersal pattern of R. microplus from Southeast Asia, the region where the species originated.